The golem's eye - Stroud, Jonathan (New York : Miramax Books/Hyperion Books for Children, 2004)
In their continuing adventures, magician's apprentice Nathaniel, now fourteen years old, and the djinni Bartimaeus travel to Prague to locate the source of a golem's power before it destroys London.
800
YALSA Best Books for Young Adults 2005
Keywords: Magic -- Fiction; Apprentices -- Fiction; Genies -- Fiction; Golem -- Fiction; Prague (Czech Republic) -- Fiction; Czech Republic -- Fiction; London (England) -- Fiction; England -- Fiction